Gagasan Pendidikan Islam Muhammad Abduh dan Hubungannya Dengan Kurikulum Merdeka di Indonesia - Nuzila Khoirun Nisa; Suci Purnama Sari; Anisah Jahro; Andi Rosa (PT. AHLAL PUBLISHER NUSANTARA, 2025)
Islamic education plays a crucial role in shaping a civilization that adapts to changing times. Muhammad Abduh, one of the Islamic reformers who placed significant emphasis on education, emphasized the importance of reason, rationality, and ijtihad in the teaching and learning process, while simultaneously rejecting the shackles of imitation (taqlid). In the Indonesian context, the Independent Curriculum (Kurikulum Merdeka), which began to be implemented in 2022, is a response to the demands of globalization, the Fourth Industrial Revolution, and the need for flexible learning that emphasizes creativity, critical thinking, and character. This study aims to analyze the relevance of Muhammad Abduh's Islamic educational thinking to the implementation of the Independent Curriculum in Indonesia. The research method employed a qualitative approach with a literature review, examining Abduh's works and contemporary literature related to the national curriculum. The study's findings indicate that Abduh's ideas, such as reason-based education, the integration of religious and modern sciences, and liberation from the shackles of imitation (taqlid), align with the principles of the Independent Curriculum, which emphasize teacher autonomy, student freedom, and competency-based learning. Furthermore, Abduh's ideas on education reform are also relevant to pressing issues in Indonesia, such as weak literacy, disparities in educational quality, and the challenges of digitalization. Therefore, Abduh's thinking can serve as a philosophical foundation for strengthening the implementation of the Independent Curriculum, while also providing a progressive Islamic nuance relevant to the nation's needs. Keywords: Muhammad Abduh, Islamic Education, Independent Curriculum, Educational Reform Abstrak Pendidikan Islam memiliki peran penting dalam membentuk peradaban umat yang adaptif terhadap perkembangan zaman. Salah satu tokoh pembaharu Islam yang memberikan perhatian besar terhadap pendidikan adalah Muhammad Abduh. Gagasannya menekankan pentingnya akal, rasionalitas, dan ijtihad dalam proses belajar-mengajar, sekaligus menolak taqlid yang membelenggu umat. Dalam konteks Indonesia, sistem Kurikulum Merdeka yang mulai diterapkan sejak 2022 hadir sebagai respons terhadap tuntutan globalisasi, revolusi industri 4.0, serta kebutuhan akan fleksibilitas pembelajaran yang menekankan kreativitas, berpikir kritis, dan karakter. Penelitian ini bertujuan menganalisis relevansi pemikiran pendidikan Islam Muhammad Abduh terhadap implementasi Kurikulum Merdeka di Indonesia. Metode penelitian menggunakan pendekatan kualitatif dengan studi kepustakaan, mengkaji karya-karya Abduh serta literatur kontemporer terkait kurikulum nasional. Hasil kajian menunjukkan bahwa gagasan Abduh, seperti pendidikan berbasis akal, integrasi ilmu agama dan ilmu modern, serta pembebasan dari belenggu taqlid, memiliki kesesuaian dengan prinsip Kurikulum Merdeka yang menekankan otonomi guru, kebebasan peserta didik, dan pembelajaran berbasis kompetensi. Selain itu, gagasan Abduh tentang reformasi pendidikan juga relevan dengan isu-isu hangat di Indonesia, seperti lemahnya literasi, ketimpangan kualitas pendidikan, serta tantangan arus digitalisasi. Dengan demikian, pemikiran Abduh dapat dijadikan salah satu landasan filosofis dalam memperkuat implementasi Kurikulum Merdeka, sekaligus memberikan nuansa Islam progresif yang relevan dengan kebutuhan bangsa. Kata kunci: Muhammad Abduh, Pendidikan Islam, Kurikulum Merdeka, Reformasi Pendidikan